Accuracy of spontaneous dynamic teacher emotion recognition by Japanese college students - Kennedy, Olivia; Kuwahara, Noriaki; Noble, Tracy; Fukada, Chie (Frontiers in Education, 2025)
This study measures how accurately Japanese university students judge the emotion expressions of both Japanese and non-Japanese teachers and how much of that judgement is based on facial expression and physical movement. Silent recordings of ten teachers spontaneously displaying emotions during authentic classroom teaching sessions were digitally processed into either motion capture (point-light display) or had their backgrounds blurred (full-light display). Both types of videos were then viewed by 118 university students aged 18–22. Participants selected the emotion that they perceived the teacher to be expressing in each video (happiness, pride, interest, surprise, irritation, stress, sadness, fear and other). Emotion recognition accuracy was higher in full-light than point-light displays for both teacher groups, except for sadness, which was significantly more accurately perceived in the point-light display. For negative emotions, perception accuracy was higher in the full-light condition compared to the point-light condition for both Japanese (27.1% vs. 18.5%) and non-Japanese teachers (22.2% vs. 13.0%). A similar trend was observed for positive emotions, where Japanese teachers in the full-light condition exhibited a higher perception accuracy (42.2%). Statistical analyses showed significant differences between conditions, with perception accuracy consistently higher in the full-light than the point-light condition in both emotion types and cultural backgrounds (p < 0.05). These findings add further evidence to the existence of the in-group advantage in recognition accuracy in spontaneous dynamic (non-static) stimulus materials. In the EFL classroom, and other similar multicultural contexts, stakeholders should be guided to make best use of any existing advantages, to allow the most mutually beneficial relationships to form and thrive. Future research should explore how these findings can be integrated into teacher training programs to foster more effective communication in classrooms, both cross- and intra-cultural.